Ecosystem Functioning Under the Influence of Bottom-Trawling Disturbance: An Experimental Approach and Field Observations From a Continental Slope Area in the West Iberian Margin - Ramalho, Sofia P.; Lins, Lidia; Soetaert, Karline; Lampadariou, Nikolaos; Cunha, Marina R.; Vanreusel, Ann; Pape, Ellen (Frontiers in Marine Science, 2020)
Understanding the effects of bottom-trawling induced changes in benthic community structure, diversity and ecosystem functioning across different benthic-size components is imperative to determine the future sustainability of bottom-trawling fisheries in deep-sea regions. In this study, we combined field sampling observations with a pulse-chase experiment on sediments obtained from two stations of interest along the West Iberian Margin (WIM) distinguished by different trawling pressures. We compared these two stations in terms of meio- and macrofauna (infauna) standing stocks, biodiversity and several ecosystem function proxies. These proxies included: (i) 13C uptake by bacterial communities, (ii) infauna respiration rates, (iii) penetration of 13C in the sediment, and (iv) sediment pore-water nutrient concentrations. The pulse-chase experimental results were complemented with a larger biological dataset partially compiled from previous studies in the area, to investigate structural and functional diversity ecosystem functioning (respiration) patterns across the WIM. Our observations indicated that different regimes of trawling pressure influenced both macrofaunal respiration rates with disturbed sediments predominantly composed of deposit-/detritus-feeding smaller-sized macrofauna species. Moreover, sediment biogeochemical functioning (ammonium profiles) and 13C bacterial uptake showed differences among the two disturbance regimes. On the contrary, the biomass of small-sized biota, including bacteria and meiofauna, did not show marked differences between stations. The general depletion in macrofauna species richness across impacted areas of the study region was also correlated with a reduction in total biomass and respiration, suggesting that the long history of trawling disturbance at the WIM may affect regulatory ecosystem functions. These preliminary findings alert for the impacts of trawling on crucial functions of benthic ecosystems that may be imperceptible to the current tools used in monitoring programs.